(untitled) (Journal of Governance and Development (JGD), 2016)
Set in post conflict northern Uganda, this paper analyses the challenges facing local communities living adjacent to Murchison Falls National Park in Acholi land as they grapple with efforts to restore their livelihoods, in view of costs and losses inflicted on them by problem animals. Their return to their villages after 20 years of the war between insurgents of Lord’s Resistance Army and the government of Uganda held a lot of promise. The state sponsored Peace, Recovery and Development Plan; donor funded projects; multinational agricultural companies setting up in the area; and the tourism revenue sharing fund; all pointed to an empowering recovery process for the local community to achieve self-reliance. However, the pain of consistent destruction of their crops by wildlife, an unfair policy on compensation of damage caused by problem animals, worsened by the government refusal to plan with the affected communities made them feel left out. This paper focuses on the Tourism Revenue Sharing Fund as a tool to analyse the costs and losses incurred by local peasants who continue to lose their agricultural livelihoods but whose appeals for dialogue continue to be ignored by the state. Data for this paper were collected using ethnographic methods that included in-depth interviews of key informants, observation, as well as both formal and informal interactions with members of the local community in Pabit parish of Purongo in Acholi sub region, and government documents.